2020
DOI: 10.1186/s12889-020-09819-7
|View full text |Cite
|
Sign up to set email alerts
|

Psychological symptoms are associated with screen and exercise time: a cross-sectional study of Chinese adolescents

Abstract: Background Mental disorders among adolescents have become a worldwide public health problem. This study aimed to estimate the best combination of exercise time and screen time to promote the mental health of Chinese adolescents. Methods Participants included 7200 Chinese adolescents aged 13–18 years from six regions of China. Screen and exercise time data were collected via a self-rated questionnaire. Psychological symptoms (e.g., often feeling dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…Moreover, too much screen time also has an impact on physical health, such as visual fatigue and dry eye. A great number of studies in children and adolescents have shown that high screen time is associated with increased risk of psychological problems ( 27 29 ). Additionally, giving more attention to media coverage of the COVID-19 outbreak is associated with higher psychological distress ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, too much screen time also has an impact on physical health, such as visual fatigue and dry eye. A great number of studies in children and adolescents have shown that high screen time is associated with increased risk of psychological problems ( 27 29 ). Additionally, giving more attention to media coverage of the COVID-19 outbreak is associated with higher psychological distress ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…observed 19 adult women with depression who experienced significant relief after 4 weeks of preferred intensity exercise rather than prescribed intensity exercise. A survey of 7200 Chinese adolescents aged 13–18 years from six regions of China also found that screen and exercise time are associated with psychological symptoms in Chinese adolescents [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Participants reported their screen time by answering the question “How many hours per day did you spend on electronic items (eg, television, computer, mobile phone, video game console) in the past month?” The question has previously shown acceptable validity and reliability in the Chinese population. 33 Daily screen time was categorized as <2 hours/day and ≥2 hours/day. 34 …”
Section: Methodsmentioning
confidence: 99%
“…The question has previously shown acceptable validity and reliability in the Chinese population. 33 Daily screen time was categorized as <2 hours/ day and ≥2 hours/day. 34 We investigated factors including demographic informations: gender (male or female), residence (urban or suburban), mode of delivery (vaginal, cesarean and unknown), frequency of vigorous physical activity including running, swimming, and playing football or basketball per week (0, 1-4, 4-7 times/ week), residence in school (yes or no), attending an afterschool tutorial program (yes or no), smoking (yes or no).…”
Section: Questionnaire Surveymentioning
confidence: 99%